The Relationship between Metabolic Syndrome and Smoking and Alcohol Experiences in Adolescents from Low-Income Households - Moonyoung Choi; Joungkyue Han; Yonghwan Kim; Jinwook Chung (MDPI AG, 2021)
Metabolic syndrome (MetS) in children and adolescents is increasing globally and the age of onset is gradually decreasing. MetS is associated with serious health problems and presents an early risk for adult morbidity and mortality. From 2014-2019, we investigated the relationship between MetS and health behaviors such as smoking, alcohol consumption, and nutrition education in Korean adolescents (boys: 1235, girls: 1087, age: 13-18 years) based on household income; the relationship with hand grip strength was also evaluated. The prevalence of MetS was 8.8% in boys and 5.1% in girls; in the lowest income households, the risk increased ~1.5-fold for boys and ~4-fold for girls, whereas risks of smoking and alcohol use increased 1.81 vs. 2.34 times, and 2.34 vs. 2.37 times for boys and girls, respectively. In adolescents with the weakest grip strength, the risk of MetS increased 9.62 and 7.79 times in boys and girls, respectively. Girls lacking nutrition education exhibited a 1.67-fold increased risk of MetS, but this was not significant in boys. Low household income increased the risk of unhealthy behaviors such as smoking and alcohol consumption in both sexes, and together with low hand grip strength, was an important predictor for developing MetS.